Identification and Characterization of HD1, a Novel Ofloxacin-Degrading Bacillus Strain - Zhang, Jing; Sha, Naiqing; Li, Yanhong; Tang, Shen; Peng, Yuqing; Zhao, Yao (Frontiers in Microbiology, 2022)
In recent years, an increasing number of lakes and soils around the world have been polluted by antibiotics, seriously threatening the ecological balance and human health. Currently, there is a lack of understanding of the biodegradation mechanism of typical antibiotics by microorganisms. In this study HD1, a novel Bacillus sp strain called capable of effectively degrading ofloxacin (OFL), a typical antibiotic with a high detection rate in the environment, was isolated from soil contaminated by OFL. The results of single-factor experiments showed that the optimal conditions for OFL degradation included 30 °C, pH 7.0, and 10 gL-1 NaCl. After 7 days of incubation under aerobic conditions, the degradation efficiency of OFL (5 mg L-1) was about 66.2 %. Five degradation products were detected by LC-MS analysis, and it was deduced that the possible degradation pathways of OFL included the oxidation of the piperazine ring, demethylation, hydroxylation, and methoxy cleavage. Metabolomics analysis indicated that key pathways with the highest difference with HD1 metabolites included the phenylalanine, arginine, and proline metabolism pathways. This study explored the degradation mechanism of OFL by HD1 and provides a theoretical basis and technical support for the remediation of OFL-contaminated environments by functional microorganisms.